HUBUNGAN MUTU PELAYANAN KEPERAWATAN TERHADAP TINGKAT KEPUASAN PASIEN DI KLINIK PRATAMA POLRES KOTA TANJUNGPINANG - Habid Al Hasbi; Ilham Kurniadi; Emy Kurniawati; Sarwoko Sarwoko; Luluk Lusiati Cahyarini (STIKES Estu Utomo, 2025)
Background: Patient satisfaction standards in health services are set nationally by the Ministry of Health in 2016 regarding Minimum Service Standards for patient satisfaction which is above 95% while the percentage of patient satisfaction index at the Tanjungpinang City Police Pratama Clinic in the last 3 years did not meet the expected index of 95%, so that the resulting impact is a reduction in the number of patient membership. Purpose: To determine the relationship between the quality of nursing services and the level of patient satisfaction at the Tanjungpinang City Police Pratama Clinic Methods: Type of quantitative research with non-experimental analytic descriptive design with a cross sectional approach. The population of this study is the number of patients recorded at level I health facilities at the Tanjungpinang City Police Pratama Clinic with accidental sampling technique. The research was conducted at the Tanjungpinang City Police Pratama Clinic in June 2024. Statistical tests using chi-square. Results: The research obtained shows that the quality of service at the Tanjungpinang City Police Pratama Clinic is mostly not good, namely 54.4%. Patient satisfaction at the Tanjungpinang City Police Pratama Clinic is mostly satisfied, namely 52.2%. Based on the results of the chi-square statistical test p value = 0.005 < ? = 0.05, thus indicating that Ho is rejected and Ha is accepted, which means that there is an influence between service quality and satisfaction. Conclusion: There is a relationship between the quality of nursing services and the level of patient satisfaction at the Tanjungpinang City Police Pratama Clinic. It is hoped that health workers, especially nurses at the Tanjungpinang City Police Pratama Clinic, will improve their empathy attitude by taking the time to communicate with patients and patients' families